2018
DOI: 10.1021/acscentsci.8b00601
|View full text |Cite
|
Sign up to set email alerts
|

Critical Assessment of the Interaction between DNA and Choline Amino Acid Ionic Liquids: Evidences of Multimodal Binding and Stability Enhancement

Abstract: Long-term storage and stability of DNA is of paramount importance in biomedical applications. Ever since the emergence of ionic liquids (ILs) as alternate green solvents to aqueous and organic solvents, their exploration for the extraction and application of DNA need conscientious understanding of the binding characteristics and molecular interactions between IL and DNA. Choline amino acid ILs (CAAILs) in this regard seem to be promising due to their non-cytotoxic, completely biobased and environment-friendly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 67 publications
10
64
0
Order By: Relevance
“…The alkyl C-H bands in the range from 2850 to 3000 cm −1 are also blue-shifted because of the pressure increase ( Figure 3b). In agreement with our experimental results, several researchers [16,19,20,24,25] suggested that [C 4 MIM] + cations can be easily bound into the minor groove structure of DNA molecules by the electrostatic force and van der Waals interactions. In comparison with pure [C 4 MIM][PF 6 ] at the pressure of 0.4 GPa (Figure 2b), the C 2 -H and C 4,5 -H absorption bands of [C 4 MIM][PF 6 ]/DNA mixture at 0.4 GPa (Figure 3b) show smaller frequency shifts under compression.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…The alkyl C-H bands in the range from 2850 to 3000 cm −1 are also blue-shifted because of the pressure increase ( Figure 3b). In agreement with our experimental results, several researchers [16,19,20,24,25] suggested that [C 4 MIM] + cations can be easily bound into the minor groove structure of DNA molecules by the electrostatic force and van der Waals interactions. In comparison with pure [C 4 MIM][PF 6 ] at the pressure of 0.4 GPa (Figure 2b), the C 2 -H and C 4,5 -H absorption bands of [C 4 MIM][PF 6 ]/DNA mixture at 0.4 GPa (Figure 3b) show smaller frequency shifts under compression.…”
Section: Introductionsupporting
confidence: 92%
“…The alkyl side chain of an imidazolium cation may participate in aggregation and association with anions in bulk ILs, although the hydrophilic and Coulomb forces remain the dominant interactions [11][12][13][14][15]. On top of that, several reports [17][18][19][20][21][22][23][24] show that the hydrophobic alkyl chains can stabilize biopolymers like nucleic acids via forming the association through electrostatic interactions between the DNA molecule and cations of IL.DNA molecules can associate with cations of IL via the negatively charged backbone and hydrophobic groove interaction of DNA [19][20][21][22][23][24]. The cluster structure of ILs can be disturbed by mixing with an additive-like DNA via electrostatic interaction between the cation head group of ILs and phosphate anion of DNA and hydrophobic association between the alkyl part of IL cation and the groove region or nitrogenous base of DNA [19][20][21][22][23][24].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Chandran et al (2012) described that the electrostatic interactions between ILs and DNA phosphate groups as well as hydrophobic and polar interactions between ILs and DNA major and minor grooves are responsible for dehydration and high stability of DNA macromolecules. More recently, Sahoo et al (2018) reported the molecular mechanism of binding between DNA and non-toxic ILs composed of a cholinium cation and amino-acid-derived anions, namely glycine, alanine, and proline. The authors showed that IL anions have a negligible effect on binding to DNA, when compared with the cholinium cation.…”
Section: Introductionmentioning
confidence: 99%